2001
DOI: 10.1136/adc.84.1.76
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre trial of recombinant growth hormone and low dose oestrogen in Turner syndrome: near final height analysis

Abstract: Background-Turner syndrome accounts for 15-20% of childhood usage of growth hormone (GH) in the UK but final height benefit remains uncertain. The most effective strategy for oestrogen replacement is also unclear. Methods-Fifty eight girls who, at start of treatment, were of mean age 9.1 years and projected final height 142.2 cm were randomised to receive in year 1, either low dose ethinyloestradiol 50-75 ng/kg/day, GH 28 IU/m 2 surface area/week as a daily injection, or a combination of ethinyloestradiol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
(11 reference statements)
1
21
0
3
Order By: Relevance
“…Our present study as well as a previous report on late GH therapy in UTS girls analyzing first-year height velocities (n = 345) and near AHs (n = 28) from KIGS clearly indicate that late initiation of GH therapy shows robust height improvement [29] disproving a preceding single center study which reported no further height gains after puberty onset in 42 UTS patients [5]. The appropriate age to induce puberty in UTS patients remains a matter of debate [8,30,31]. Initiation of GH treatment early allows timely estrogen supplementation and prevents further height loss in childhood and adolescence and therefore might reduce the psychological harm of short stature and hypogonadism [33,34].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our present study as well as a previous report on late GH therapy in UTS girls analyzing first-year height velocities (n = 345) and near AHs (n = 28) from KIGS clearly indicate that late initiation of GH therapy shows robust height improvement [29] disproving a preceding single center study which reported no further height gains after puberty onset in 42 UTS patients [5]. The appropriate age to induce puberty in UTS patients remains a matter of debate [8,30,31]. Initiation of GH treatment early allows timely estrogen supplementation and prevents further height loss in childhood and adolescence and therefore might reduce the psychological harm of short stature and hypogonadism [33,34].…”
Section: Discussionmentioning
confidence: 95%
“…Management of puberty was also studied in detail. After starting estrogen treatment for the induction of puberty further height gain may be limited [5,6,7], but other studies investigating the age at induction of puberty suggested different results [8,9]. The actual therapeutic guidelines [10] recommend an early initiation of GH treatment after the age of 2 years as soon as the height of a patient with UTS falls below the third percentile of the growth chart for healthy females.…”
Section: Introductionmentioning
confidence: 99%
“…Another, controlled study of 232 Turner subjects reported increases in first year growth velocity of less than 3 cm/year compared with that of a control group and without a significant difference between GH doses of 0.12 or 0.15 IU/kg per day [19]. An additional study in Turner syndrome reported a first year treatment gain in height of 0.7 SDS at a GH dose of 0.14 IU/kg per day [20]. Using more extreme GH dosing seems to increase the first year response.…”
Section: Comparison With Short-term Effect Of Gh Treatment In Turner mentioning
confidence: 99%
“…In the study by Albanese and Stanhope [10], only 2 of 34 girls with CDGP received estrogen treatment. In other patient groups, such as in those with Turner syndrome or hypogonadism, early supplementation of low-dose estrogen has not been shown to negatively affect adult stature [39,40]. Accordingly, in our study, there was no difference in AH or TH attainment between the subjects with CDGP who were treated with low-dose estrogen and those girls who did not receive treatment.…”
Section: Discussionmentioning
confidence: 42%